A retrospective study on data from animal-related complaints, abuse, cruelty, trafficking and trade received by Animal Welfare Organizations in Singapore in 2016 / Elizabeth X. Chang and Paola A. Magni - Chang, Elizabeth X.; Magni, Paola A. (Faculty of Medicine, 2021)
Introduction: Singapore is a first-world country, protected by an advanced police force, competent in investigating crime against human citizens. Little is known about crime against animals and what Singapore does in these instances. Methods: This research considered data from reports of various animal crime that occurred in 2016 as recorded by the three animal welfare organizations appointed to investigate crimes against animals (AVS, SPCA and ACRES). Details of the cases collected were sorted using eight parameters: date, location, perpetrator, victim, type of crime or complaint, case outcome, organization, and punishment. The type of crime or complaint were divided into the categories: abandoned, allowed to roam, barking animal, caged, poor conditions, sick and untreated, physically abused, poisoned, deceased, taken from the wild, illegal possession, illegal sale, smuggling, and licencing. Results: In 2016, a total of 831 cases committed by 839 perpetrators were reported, for a total of 2357 minimum number of animals involved, comprehensive of animal parts and items made from animals. The largest proportion of the cases occurred against domestic animals and in housing districts. Despite these high numbers, only perpetrators in 11 cases were charged with fines and/or imprisonment time. Conclusions: This research paints, for the first time, a picture of what animal crime looks in the Singaporean society. Results are of pivotal importance to identify criminal hot spots, most common type of crimes, and animal categories that are most often victimised, aiming to facilitate the work of the organizations involved in investigating animal-related crime in Singapore.